Eschatological Awareness as a Psychological Mechanism for Developing Students' Self-Control in Islamic Character Education - Kusmana Kusmana; Entis Sutisna; Anwar Musthofa; Rofiq Rodlian Mussabiq Firdaus; Ridwan Ridwan (Journal of Mandalika Social Science, 2026)
Strengthening character education has become a key priority in Islamic education amid increasing concerns about students’ behavioral misconduct in social and digital environments. Although previous studies have established positive relationships between religiosity, faith, self-regulation, and self-control, limited attention has been given to the specific psychological processes through which belief in the Hereafter may contribute to students’ self-control. In particular, eschatological awareness has rarely been conceptualized as an integrative construct linking Islamic aqidah, religious psychology, and character education. This study aims to analyze eschatological awareness from the perspective of Islamic aqidah, examine its theoretical relevance to religious psychology and self-control, and propose a conceptual model for Islamic character education. Employing a qualitative library research design, the study draws on the Qur’an, Hadith, aqidah literature, and scholarly publications on eschatology, religious psychology, self-control, self-regulation, and Islamic character education. Data were analyzed through content analysis and conceptual analysis. The findings suggest that the internalization of belief in accountability in the Hereafter may develop into eschatological awareness, which fosters moral awareness and muraqabah as internal processes supporting self-regulation and self-control. Strengthened self-control, in turn, contributes conceptually to the development of Islamic character. The study proposes an eschatological awareness–based conceptual model that provides an integrative theoretical framework connecting Islamic aqidah, religious psychology, and Islamic character education.